Insignificant Effect of Isolated Hypothyroxinemia on Pregnancy Outcomes During the First and Second Trimester of Pregnancy - Chen, Liangmiao; Yang, Hong; Ye, Enling; Lin, Zhenzhen; Peng, Mengmeng; Lin, Hai; Yu, Lechu; Cai, Zhuhua; Lu, Xuemian (Frontiers in Endocrinology, 2020)
Objective Adverse maternal outcomes and perinatal complications are associated with overt and subclinical maternal hypothyroidism. It is not clear whether these complications also occur in women with isolated hypothyroxinemia during pregnancy. The aim of this study was to evaluate the effects of isolated hypothyroxinemia on maternal and perinatal outcomes during pregnancy. Methods This study included data from 2864 pregnant women in the first trimester (67 women with isolated hypothyroxinemia, 784 euthyroid women) and the second trimester (70 women with isolated hypothyroxinemia, 1943 euthyroid women) of pregnancy. Maternal serum samples were collected in the first and second trimester to examine thyroid hormone concentration. Hypothyroxinemia was defined as a normal maternal thyroid-stimulating hormone concentration with a low maternal free thyroxine concentration and negative thyroid autoantibodies. The following maternal outcomes were recorded: gestational hypertension, gestational diabetes mellitus, placenta previa, placental abruption, prelabor rupture of membranes, and premature delivery. Perinatal outcomes, including fetal growth restriction, fetal distress, low birth weight, intrauterine fetal death, and malformation, were also recorded. The incidence of adverse pregnancy outcomes and perinatal complications were compared between women in the first trimester and second trimester with isolated hypothyroxinemia. Results There were no significant differences in the incidence rates of adverse maternal outcomes and perinatal complications between patients in the first and second trimesters with isolated hypothyroxinemia. Conclusion The results of this study indicate that isolated hypothyroidism does not increase the incidence of adverse maternal outcomes and perinatal complications.